Friendship Design Thinking of the Prophet Muhammad Inspirational Hadith of the Prophet - Nur Fadiyah Rahmiyanti; Ahmad Izzan (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the inspiration for the hadith of the Prophet. in life. This research method is qualitative through literature and field studies with the hadith design thinking approach. The results and discussion of this research include social ethics in friendship, hadith inspiration and the example of the Prophet. in making friends, and innovation in maintaining friendships. This research states that the hadith of the Prophet SAW. have inspirational messages in the life of friends to the relationship of a friendship to the hereafter